2014
DOI: 10.1037/a0036666
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in judgments of inappropriate behavior are related to humor style preferences.

Abstract: Identifying social gaffes is important for maintaining relationships. Older adults are less able than young to discriminate between socially appropriate and inappropriate behavior in video clips. One open question is how these social appropriateness ratings relate to potential age differences in the perception of what is actually funny or not. In the present study, young, middle-aged, and older adults were equally able to discriminate between appropriate and inappropriate social behavior in a diverse set of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Consistent with this idea, declines in emotion recognition mediate age differences in other social insights, including older men's verbosity (Ruffman, Murray, Halberstadt, & Taumoepeau, 2010), older adults' understanding of social gaffes (Halberstadt, Ruffman, Murray, Taumoepeau, & Ryan, 2011; although see Stanley, Lohani, & Isaacowitz, 2014 for evidence that older adults do not always find social gaffes harder to identify), and older adults' lie detection (Ruffman, Murray, Halberstadt, & Vater, 2012). The explanation given for these relations is that difficulty detecting emotional cues makes it more likely that one will continue to talk despite emotional cues to stop (verbosity), fail to understand how certain AGE DIFFERENCES IN RWA 7 things make others feel uncomfortable and therefore should not be said (social gaffes), or detect emotional leaks in liars.…”
mentioning
confidence: 96%
“…Consistent with this idea, declines in emotion recognition mediate age differences in other social insights, including older men's verbosity (Ruffman, Murray, Halberstadt, & Taumoepeau, 2010), older adults' understanding of social gaffes (Halberstadt, Ruffman, Murray, Taumoepeau, & Ryan, 2011; although see Stanley, Lohani, & Isaacowitz, 2014 for evidence that older adults do not always find social gaffes harder to identify), and older adults' lie detection (Ruffman, Murray, Halberstadt, & Vater, 2012). The explanation given for these relations is that difficulty detecting emotional cues makes it more likely that one will continue to talk despite emotional cues to stop (verbosity), fail to understand how certain AGE DIFFERENCES IN RWA 7 things make others feel uncomfortable and therefore should not be said (social gaffes), or detect emotional leaks in liars.…”
mentioning
confidence: 96%
“…Later, Ruch et al () found that age and gelotophobia had a negative correlation, by the measure of Pho‐Phi‐Kat. In addition, past studies have found that people over the age of 35 had higher scores related to using positive humour styles but had lower scores related to hostile humour styles than did young adults (17–21 years old) (Damianakis & Marziali, ; Stanley, Lohani, & Isaacowitz, ). In general, negative laugh‐related traits (i.e., fear of being laughed at, enjoying laughing at others) become weaker with age.…”
Section: Gender Differences On Laugh‐related Traitsmentioning
confidence: 97%
“…Inappropriate behaviors have been witnessed in physicians (77%) and in nurses (65%) . Inappropriate behavior of health care workers, such as aggression, is a contributing factor that increases the risk of making errors, causing delays in delivery of care or conflict and stress for health care workers . In Rosenstein and O'Daniel's study of 1487 health care workers, 75% of respondents believed that medical errors caused by disruptive behavior could have been prevented, and 60% reported that they personally knew of at least one error that occurred because of disruptive behavior .…”
Section: Patient Safety and Inappropriate Behaviorsmentioning
confidence: 99%
“…20 Inappropriate behavior of health care workers, such as aggression, is a contributing factor that increases the risk of making errors, causing delays in delivery of care or conflict and stress for health care workers. 14,21,22 In Rosenstein and O'Daniel's study of 1487 health care workers, 75% of respondents believed that medical errors caused by disruptive behavior could have been prevented, and 60% reported that they personally knew of at least one error that occurred because of disruptive behavior. 23 Another study that included 4530 health care workers showed that 27% felt there was a linkage between disruptive behavior and patient mortality, 67% believed that disruptive behaviors and adverse events are linked together, and 71% felt that disruptive behaviors can be linked to medical errors.…”
Section: Pat I E N T S a F E Ty A N D I N A P P Ro P R I At E B E H Amentioning
confidence: 99%